Implementasi Penguatan Pendidikan Karakter Melalui Ekstrakurikuler Pembelajaran Pendidikan Agama Islam (PAI) di SMP Swasta Kencana Sastra Percut Sei Tuan - Astriana Hidayah; Ali Imran Sinaga; Makmur Syukri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to analyze the implementation of strengthening character education through extracurricular activities of reading and writing the Qur'an (BTQ) in Islamic Religious Education (PAI) learning at school. Strengthening character education is the main focus in an effort to form students who have religious values, discipline, and the value of reading. BTQ activities are chosen as one of the effective methods to instill these values systematically and sustainably. The research method used is descriptive qualitative research method with data collection techniques through interviews, observation, and documentation. The subjects of this study consisted of principals, BTQ extracurricular teachers, deputy curriculum, and students. The results showed that BTQ extracurricular activities are effective in strengthening student character. Through learning to read and write the Qur'an, students not only develop religious skills but also experience strong character building, such as religious values, discipline, and love of reading. This implementation is supported by the active role of PAI teachers and the support of the school environment, but also faces several obstacles, such as time constraints and lack of student motivation. This study suggests an increase in parental involvement in supporting BTQ activities at home as well as additional time and adequate facilities to support the smooth running of these activities. Thus, it is expected that strengthening character education through BTQ can run more optimally and have a greater positive impact on students' character development.